Clinical Impact of External Laryngeal Manipulation During Laryngoscopy on Tracheal Intubation Success in Critically Ill Children*. Issue 2 (February 2018) - Kojima, Taiki; Laverriere, Elizabeth K.; Owen, Erin B.; Harwayne-Gidansky, Ilana; Shenoi, Asha N.; Napolitano, Natalie; Rehder, Kyle J.; Adu-Darko, Michelle A.; Nett, Sholeen T.; Spear, Debbie; Meyer, Keith; Giuliano, John S.; et al.
Abstract : Objectives: External laryngeal manipulation is a commonly used maneuver to improve visualization of the glottis during tracheal intubation in children. However, the effectiveness to improve tracheal intubation attempt success rate in the nonanesthesia setting is not clear. The study objective was to evaluate the association between external laryngeal manipulation use and initial tracheal intubation attempt success in PICUs. Design: A retrospective observational study using a multicenter emergency airway quality improvement registry. Setting: Thirty-five PICUs within general and children's hospitals (29 in the United States, three in Canada, one in Japan, one in Singapore, and one in New Zealand). Patients: Critically ill children (< 18 years) undergoing initial tracheal intubation with direct laryngoscopy in PICUs between July 1, 2010, and December 31, 2015. Measurements and Main Results: Propensity score–matched analysis was performed to evaluate the association between external laryngeal manipulation and initial attempt success while adjusting for underlying differences in patient and clinical care factors: age, obesity, tracheal intubation indications, difficult airway features, provider training level, and neuromuscular blockade use. External laryngeal manipulation was defined as any external force to the neck during laryngoscopy. Of the 7, 825 tracheal intubations, the initial tracheal intubation attempt was successful in 1, 935/3, 274 intubations (59%) with external laryngeal manipulation and 3, 086/4, 551 (68%) without external laryngeal manipulation (unadjusted odds ratio, 0.69; 95% CI, 0.62–0.75; p < 0.001). In propensity score–matched analysis, external laryngeal manipulation remained associated with lower initial tracheal intubation attempt success (adjusted odds ratio, 0.93; 95% CI, 0.90–0.95; p < 0.001). Conclusions: External laryngeal manipulation during direct laryngoscopy was associated with lower initial tracheal intubation attempt success in critically ill children, even after adjusting for underlying differences in patient factors and provider levels. The indiscriminate use of external laryngeal manipulation cannot be recommended.